Tacit knowledge in unstructured decision process - Fábio de Oliveira Lucena; Silvio Popadiuk (RAUSP Management Journal, 2020)
Purpose – This paper aims to identify the expressions and flows of tacit knowledge in the unstructured decision process. In this type of process, decision-makers use not only the explicit knowledge but also aspects such as intuition, experience and other forms of tacit knowledge. The research developed a qualitative approach, through a study of multiple cases, and applied semi-structured interviews to ten executives. The analysis of data was carried out according to Flores (1994) interpretative analysis of text technique. Results indicated that there was the insertion of tacit knowledge in all unstructured decision-making routines. It was also detected the need to explicitly add the routine of evaluation to the Mintzberg et al.’s (1976) model as elements of tacit knowledge were also identified at this stage of the decision-making process. Design/methodology/approach – The research has taken a qualitative approach, through a study of multiple cases, applying semi-structured interviews to ten executives. The analysis of data was carried out according to technique for interpretative analysis of the text. Findings – Results indicated that there was tacit knowledge in all unstructured decision-making routines. Also detected was the need to explicitly add the routine of evaluation to the model. Research limitations/implications – It was unable to perform psychological studies to investigate the deepest cognitive and emotional aspects of managers, and it does not address, in depth, some issues that are related to tacit knowledge in decisions and that would be considered relevant. Practical implications – Although this research was unable to dissect the composition of tacit knowledge in unstructured decision process, a better understanding of the aspects that make up the knowledge in question has been developed, providing some decision-making guidelines to managers. Social implications – The language between communications actors can share decision-making rules to assist in the production and process of arguments necessary for the debate, evaluation and attribution of institutionally recurrent decisions. Originality/value – The original contribution is present in a detailed description of the expressions of flows of tacit knowledge in unstructured decision-making processes, based on the model of Mintzberg et al. (1976). From the influence of tacit knowledge, it was found that the model in question needs to consider the relevance of the evaluation phase, as a stage equivalent to the other described by Mintzberg et al. (1976). These aspects have been better explained in the introduction and conclusion. Participant observation was not possible because the decision had already been taken by the informant at the moment of the interviews.